2020
DOI: 10.1038/s41427-020-00243-2
|View full text |Cite
|
Sign up to set email alerts
|

Designing artificial sodium ion reservoirs to emulate biological synapses

Abstract: Emulating neurons/synapses in the brain is an important step to realizing highly efficient computers. This fact makes neuromorphic devices important emerging solutions to the limitations imposed by the current computing architecture. To mimic synaptic functions in the brain, it is critical to replicate ionic movements in the nervous system. It is therefore important to note that ions move easily in liquids. In this study, we demonstrate a liquid-based neuromorphic device that is capable of mimicking the moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…A resistance of more than about 1 kΩ and a resistance window of about 100 times were extracted from the read voltage. We confirmed that simple synaptic functions, such as paired-pulse facilitation (PPF), could be implemented in the dynamic curve, and the transition from short-term plasticity (STP) to long-term plasticity (LTP) was based on the excessive electrical stimulation [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 60%
“…A resistance of more than about 1 kΩ and a resistance window of about 100 times were extracted from the read voltage. We confirmed that simple synaptic functions, such as paired-pulse facilitation (PPF), could be implemented in the dynamic curve, and the transition from short-term plasticity (STP) to long-term plasticity (LTP) was based on the excessive electrical stimulation [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 60%
“…In addition, the ioncharging phenomenon can be utilized for liquid-based memory devices (Figure 1b). 48 Device conductivity is controlled by regulating the concentration of ions in the solution using ion reservoirs. A device that controls the ion concentration can also be designed as a two-terminal structure.…”
Section: Liquid-based Memory Devicesmentioning
confidence: 99%
“…Thus far, only a few studies have reported the synaptic decay characteristics, where different decay behavior was demonstrated by controlling material properties such as defects and crystallinity. Most recent biology-inspired synaptic devices have been demonstrated to emulate the Ca 2+ dynamics of organic cells; ion reactions were demonstrated in ion-gating synaptic transistors or liquid-based memory. The ion- or liquid-based synaptic devices need new and diverse methods so that the electrode reliably connects the external circuit and the synaptic array, and the ionic device can be fabricated with the actual synaptic size while controlling the amount of ionic liquid. Ga is one of the abundant elements on earth, has low cost, and exhibits a stable structure when oxidized.…”
Section: Introductionmentioning
confidence: 99%